Kurikulum Pendidikan Budaya pada Satuan Pendidikan Rintisan - Sutjipto -- (Jurnal Pendidikan dan Kebudayaan, 2013)
This study aims to obtain a picture related to the implementation of the cultural curriculum development efforts 300 units on preschool education, primary education, secondary education, exceptional education, and educational equality that has been developed as a pilot model in 2012. The technique used in this study include descriptive study. A descriptive study with critical discourse analysis, in the sense of collecting facts and study the situation, outlook, and ongoing process. The main information collected through secondary data such as documentation reports, the results of focus group discussions, and participant observation. Data processed by the implementation of activities, and the results of the model unit activity throughout the pilot study culture curriculum implementation. Data analysis techniques used description, and interpretation. Results showed that: 1) the growth of a culture growing in a positive direction; 2) norms and values are implemented affects not only the daily activities, but also to motivate and encourage; 3) norms and values not only serves as a means of interadhesive one another, but also beneficial for the improvement of social skills; 4) norms and values as the foundation footing to build a more advanced civilization and humane for the future seemed to be entrenched; and 5) the willingness of stakeholders spool still be a problem in the implementation.Â ABSTRAKÂ Penelitian ini bertujuan untuk memperoleh gambaran terkait dengan upaya pengembangan implementasi kurikulum pendidikan budaya pada 300 satuan pendidikan pada jenjang prasekolah, pendidikan dasar, pendidikan menengah, pendidikan luar biasa, dan pendidikan kesetaraan yang telah dikembangkan sebagai model rintisan tahun 2012. Penelitian berbentuk deskriptif dengan analisis wacana kritis, dalam arti menghimpun fakta dan mempelajari situasi, pandangan, dan proses yang sedang berlangsung. Informasi utama dikumpulkan melalui data sekunder seperti dokumentasi laporan, hasil fokus grup diskusi, dan pengamatan terlibat. Teknik analisis data yang digunakan deskripsi, dan interpretasi. Hasil penelitian menunjukkan bahwa: 1) makin berkembang tumbuhnya budaya ke arah yang positi; 2) norma dan nilai-nilai yang diimplementasikan berpengaruh tidak hanya pada kegiatan setiap hari, tetapi juga memotivasi dan menyemangati; 3) norma dan nilai-nilai tidak saja berfungsi sebagai sarana perekat satu sama lain antarkomunitas, tetapi juga bermanfaat untuk peningkatan keterampilan sosial; 4) norma dan nilai-nilai sebagai pijakan fondasi untuk membangun peradaban yang lebih maju dan humanis bagi masa depan tampak mulai membudaya; dan 5) kemauan pemangku kepentingan yang masih menjadi kelindan masalah dalam pengimplementasian.